Cemented hemi-arthroplasty for unstable intertrochanteric fractures in the elderly: a retrospective study - Patra, Satya R.; Panigrahi, Naresh K.; Manoj, Madini; Samant, Saswat; Bamidi, Hemanta K.; Das, Kishore C.; Mohanty, Siddhartha S. (International Journal of Research in Orthopaedics, 2020)
Background: Unstable intertrochanteric fractures belonging to 31A2 and A3 varieties are difficult challenges for orthopaedic surgeons, particularly in the elderly patients. Osteosynthesis by dynamic hip screw or proximal femoral nail are often plagued by complications like screw cut-out, excessive collapse and fixation failures due to osteoporotic bones. Because of these complications, patients are often kept confined to the bed which may increase the risks of pressure sores, venous thrombosis and pulmonary infections. So, it is desirable to mobilize these elderly patients as quickly as possible following surgery. In recent decades, primary hemi-arthroplasty has emerged as a valuable treatment option for mobilizing these patients early. Methods: We present our retrospective study on 27 patients above 60 years of age, who were managed with cemented bipolar hemi-arthroplasty after sustaining unstable intertrochanteric fractures. All the patients were operated through modified Hardinge approach. The fractured fragments were secured by stainless steel wiring, particularly the greater trochanter, wherever necessary. Results: Twenty-three patients (85%) were able to stand up with walkers by third post-operative day and were able to walk by fifth post-operative day. There was one case of hip dislocation; it was reduced under anaesthesia. No other complications were encountered at an average follow-up of 3.1 years. The Harris hip score was ‘good’ or ‘excellent’ in more than 60% patients. Conclusions: Cemented hemi-arthroplasty appears to be a reliable treatment method for unstable intertrochanteric fractures in the elderly and it allows early weight-bearing and rehabilitation in most patients following surgery.